Practice and Exploration of Market-oriented Profit Models for Virtual Power Plants in Shanghai - LI Qing, DONG Yufang, LIU Ziteng, SHI Zhihao, WANG Xiang, FAN Shuai, HE Guangyu (Dianli jianshe)
Integrating a high proportion of renewable energy to achieve dual-carbon strategic goals has resulted in new challenges for the regulatory capability of power systems. Virtual power plants （VPPs） have extensive industrial applications as an effective means of exploiting demand-side flexible resources. However，the current application scenarios of VPPs are relatively simple and a market-oriented profit model for sustainable operations has not yet been established. To promote the market-oriented development of VPPs，a series of policies has been introduced by the government at all levels. Focusing on the actual situation in Shanghai，this paper first summarizes the construction and development of VPPs and introduces the achievements and development directions of the various VPP practices followed in Shanghai. Second，according to the domestic market development situation，the profit models of VPPs participating in the demand response，spot markets，and ancillary service markets are analyzed，and a brief outlook is provided on the future expandable business of VPPs. Furthermore，a market-oriented profit model for VPPs participating in multiple market types is established to improve their operating benefits by reusing the regulation capabilities in different scenarios. Finally，the effectiveness and feasibility of the proposed model are verified through case studies. The results of this study are significant for promoting the market-oriented development of VPPs，improving the regulation capability of power systems，and achieving sustainable development goals.